Pendeteksian Financial Statement Fraud dengan Menggunakan F-Score Model : Perspektif Fraud Pentagon Theory - Ruci Arizanda Rahayu; Wiwit Hariyanto; Istian Kriya Almanfaluti (Politeknik Ganesha Medan, 2023)
This study aims to determine the partial effect of financial stability, financial targets, ineffective of monitoring, quality of external audit, change in auditors, change in directors, frequency number of CEO's picture on financial statement fraud in mining companies listed on the IDX. 2021. This study used a quantitative approach and the sample collection method in this study used purposive sampling and obtained as many as 18 companies as samples. The type of data used in this study is secondary data sourced from the company's financial reports and annual reports obtained directly from the Indonesia Stock Exchange (IDX). The data analysis method used is multiple regression analysis which is processed using the SPSS program. Based on the results of research conducted on 18 mining sector companies for the 2020 and 2021 periods it concluded that the financial stability variable as measured by ACHANGE did not have a significant effect on financial statement fraud, the financial target variable as measured by ROA had a significant effect on financial statement fraud, the ineffective variable of monitoring measured by BDOUT has no significant effect on financial statement fraud, the quality of external audit variable as measured by AUD has no significant effect on financial statement fraud, the change in auditor variable as measured by CPA has no significant effect on financial statement fraud, the change in director variable as measured with DCHANGE it has no significant effect on financial statement fraud and the frequency number of CEO's picture variable has no significant effect on financial statement fraud.